Sea piracy and maritime security challenges in the gulf of guinea, 1999 - 2018 - Chidozie Ezeozue (Journal of Management and Science, 2021)
This study has examined sea piracy and maritime security challenges in the Gulf of Guinea, 1999 – 2018. Available literature and secondary data confirms that Gulf of Guinea continues to remain an area of high concern in the area of sea piracy and maritime security challenges. High profile attacks in the Gulf of Aden, off the Horn of Africa waters, and in the Gulf of Guinea (GG), are mostly caused by Nigerian pirates and thus have elicited renewed international attention to the problems of piracy in the waters of Africa.This study was carried out to ascertain the extent to which hostage taking, oil theft and armed robbery at sea affected the security of vessels in the Gulf of Guinea. The data was analyzed using the quantitative descriptive method; also logical data framework was inclusive that shows the entire study at a glance. Consequently, empirical literature and various analyses in this study revealed that hostage taking, oil theft and armed robbery at sea, have affected the security of vessels in the Gulf of Guinea. The study also found that maritime insecurity in the region have adversely affected investment in the area particularly Nigeria; such as shipping of cargo goods, fishing trawlers, crude oil tankers among other; this allows the development of illegal offshore trade in crude oil and refined petroleum; consequently. Therefore, on the basis of the above analysis, the study concludes that hostage taking, oil theft and armed robbery at sea have significant effect on the security of imperative for Gulf of Guinea states to elect a proactive and pre-emptive leadership that would leverage on their oil affluence to address the problems of unemployment, poverty and deprivation especially in riverine communities, which incubate maritime afflictions.